How does the implementation of multiple intelligences theory with first graders hold their positive attitude towards English at I. E. Sagrado Corazón (2016)
ABSTRACT: Recognition of different learning styles is one of the biggest challenges for teachers today and taking into account intelligence is a concept wider than only to be good with numbers or letters. In my case, the awareness of these differences in the students propitiated a pleasant environment with a positive attitude. This paper reports an action research study conducted in first grade in a public school intended to hold this positive attitude through the implementation of activities based on Multiple Intelligence Theory (MIT). The data was collected through one teaching journal, one check list with the Cooperating Teacher‟s observations and one students‟ survey. The findings indicated the high degree of motivation teachers can achieve when the students‟ abilities and talents are encouraged.